2022
DOI: 10.1021/acsami.1c21742
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Transition-Metal Columbite-Tantalite as a Highly Efficient Electrocatalyst for Water Splitting

Abstract: We successfully report a liquid−liquid chemical reduction and hydrothermal synthesis of a highly stable columbite-tantalite electrocatalyst with remarkable hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) performance in acidic media. The reduced Fe 0.79 Mn 0.21 Nb 0.16 Ta 0.84 O 6 (CTr) electrocatalyst shows a low overpotential of 84.23 mV at 10 mA cm −2 and 103.7 achieved at 20 mA cm −2 current density in situ for the HER and OER, respectively. The electrocatalyst also exhibited low Tafel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Table 4 is the result for FeTa 2 O 6 (mp-31755), an ordered tapiolite [71], a cation-ordered derivative of the rutile structure [72,73], of which antiferromagnetism was investigated [72,[74][75][76][77]. Its space group P 4 2 {mnm was found as the first scored one.…”
Section: Conceptmentioning
confidence: 99%
“…Table 4 is the result for FeTa 2 O 6 (mp-31755), an ordered tapiolite [71], a cation-ordered derivative of the rutile structure [72,73], of which antiferromagnetism was investigated [72,[74][75][76][77]. Its space group P 4 2 {mnm was found as the first scored one.…”
Section: Conceptmentioning
confidence: 99%
“…Table 4 is the result for FeTa 2 O 6 (mp-31755), an ordered tapiolite [70], a cation-ordered derivative of the rutile structure [71,72], of which antiferromagnetism was investigated [71,[73][74][75][76]. Its space group P 4 2 {mnm was found as the first scored one.…”
Section: Retrieval Accuracies Of Space Group and Local Atomic Environ...mentioning
confidence: 99%
“…In this review, we first introduce the basic mechanism of water electrolysis with manganese-based catalytic materials and then systematically summarize the design strategy of manganese-based electrocatalysts to deal with the existing shortcomings of their applications. Although manganese-based materials have great potential as catalysts for water electrolysis, many challenges remain to be solved [ 110 , 111 , 112 ]. We concluded that the broad strategy is currently interface engineering and defect engineering.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%